BUDAYA AUSTRONESIA DI PAPUA - Suroto, Hari (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
Papua has a strategic location in the western Pacific region, as a connector between South East Asia and Pacific Region that makes it a strategic place to transit from both west and east. On 1500 to 1000 BC there were a new wave of migration from Austronesia. The colonist left a vivid track about their journey through ocean and islands which can be seen form their archaeological sites. These sites were found in Admiralty island on the north of New Guinea to the east of Samoa island on West Polynesia. The strongest evidence on the migration of the Austronesian in Pacific is the language. The imigrant from Austronesia who came to Pacific settled accross the coastal area of north Papua. The influence of Austronesian culture in Papua that is only on north coast Papua, the Cendrawasih bay and the Bird’s Head Peninsula is particularly the Melanesian language, which actually a development of local Papua language influenced by the Austronesian language. Other influence they made is the tradition of the making and utilization of vessels. It is because this tradition was widely unknown in mid Papua mountains and south-coast Papua. Then the other Austronesian characteristics are the structured hierarchical organization, which applied hereditary and tattoo tradition.